Numerical Investigation of Optical Burst Switching - Milan Dado; Stanislav Krajci; Jozef Dubovan; Dusan Sabol (Communications - Scientific letters of the University of Zilina, 2008)
The simulation analysis of aphysical layer of the “all optical burst switching” using aVPI Photonics™ simulation program is presented in this article. The optical burst networks adopt dedicated control channel to transmit headers of burst, at the same time the payload is transmitted on the other optical data channels after the offset time. We have proposed OBS network with four data channels and one control channel consisting of the following main optical elements: lasers with external modulation, awavelength converter using Kerr effect cross phase modulation (XPM) in optical semiconductor amplifiers (SOA), awavelength switch 4x4 and photodetector. We present the main connection of the OBS network, data and control message flow, processing in the core node and sending to next node. The results are visualized in graphs.